Bergsonian Study: Time Experience According to Adolescence in Mansfield’s Stories - Maryam Jafari; Shiva Zaheri Birgani; Mahnaz Soqandi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
With the advent of modernism and new philosophical and scientific ideas, the concept of time was treated in a new way. Bergson’s philosophy about time had a great influence on modernist writers and artist. One of the writers who were influenced by him is Katherine Mansfield. Therefore we could see Bergson’s theory of time used by her in her stories to convert her own messages. Katherine Mansfield was one of these writers that made use of different techniques in her stories in order to show time. She was much influenced by the French philosopher Henri Bergson and made use of his thoughts in her stories. This paper is going to present how Mansfield shows the concept of time in her stories and what strategies she uses to show the inner time and outer time of her characters. The study also wants to show effects of time on her characters and how being in a certain age of life, status and class in society affects the perceiving of time in people. The major concern of these stories is to show the significance of time according to Bergson’s linear and subjective theory of time. These stories show how characters experience duration in their mind and how the linear passage of time mainly affects them. The main purpose of this paper is to study the notion of time according to Bergson’s linear and subjective time in Mansfield’s stories. According to this theory there are two kinds of time, the spatial time and duration (inner time). Reality is only in the duration of individuals and the only way to achieve freedom is through duration.